The Effect of Integrated Ball Training on Improving the Physical Condition of Futsal Athletes at Skensa Futsal Academy - Muhammad Prana Mahendra Supriyanto; Bhayu Billiandri (Jurnal Master Penjas & Olahraga, 2026)
Physiological conditions are crucial for supporting the performance of futsal athletes who require speed, agility, and endurance. This study aims to determine the effect of integrated ball training on the physical condition of futsal athletes at the Skensa Futsal Academy. The method used was an experiment with a pretest-posttest control group design, involving 30 athletes through total sampling. The training program lasted for six weeks with three sessions per week. Measurements were carried out using the 50-meter run test, the Illinois Agility Run, and the 2400-meter run. Data analysis used the Shapiro–Wilk test, homogeneity test, and paired t-test in SPSS 26. The results showed a significant increase in the experimental group (p < 0.05), indicated by a decrease in time across all tests. The study's results demonstrated the superiority of integrated ball training over traditional methods, as it combines physical and skill components simultaneously.